MITIGASI DAN PEMBERDAYAAN MASYARAKAT DALAM UPAYA MENINGKATKAN KESIAPSIAGAAN TANGGAP DARURAT KEBAKARAN DI RW 11 KAMPUNG CIBODAS KELURAHAN UTAMA CIMAHI SELATAN - Wahyudi, Payzar; Nurjaman, Ujang; Setyoko, Sadono (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2025)
The number of fire incidents in residential areas, especially in the South Cimahi sub-district, is quite high. In the last year, there have been three fire incidents in Utama Village, South Cimahi Sub-district. This phenomenon indicates that the risk of fire in the community is still high, coupled with a lack of awareness and knowledge from the community itself. The purpose of this community service is to increase community awareness and preparedness for the risk of fire hazards. This community service is carried out through socialization and counseling methods as well as demonstrations of the use of fire extinguishers. This community service has output targets in the form of increased community knowledge, videos of the activity implementation and published journal articles. The community service that has been implemented is expected to significantly increase the knowledge of the 20 participants who attended. The results of the Pretest and Posttest showed a significant increase from an average score of 40 to 85 after being given counseling. The community also has new skills, namely being able to demonstrate how to use fire extinguishers and recognize various types of risk hazards in the home that can trigger fires, especially those caused by gas and electricity